Perceptions spatiales dans Corinne de Germaine de Staël (1807) - Seth, Catriona (Verbum – Analecta Neolatina, 2014)
Germaine de Staël’s 1807 novel, Corinne ou l’Italie, is concerned with space in more ways than one. The title indicates the primary importance of Italy – a fragmentary collection of states at the time. Rome is the axis around which the heroine’s life initially seems to revolve. The novel then sets up various poles to counterbalance or complement it: Oswald is Scottish and the aesthetics of Ossian plays a part in the work’s poetics; French pre-revolutionary culture is also shown as important in an ideal cultural mix. Staël is looking to the future in this work, which implicitly imagines a new balance of power for Europe.